Government Support for Formation of Innovative Strategy in Industrial Enterprises - Djumanazarovna, Xasanova Gulruh; Muhammedrizayevna, Tairova Mavluda; Dehqonboyevich, Qudratov Aziz (International Journal of Psychosocial Rehabilitation, 2020)
The article discusses the importance and objective necessity of forming an innovation strategy in industrial enterprises at the current stage of economic development. Because in the current conditions, when the volume of traditional, limited, non-renewable economic resources is declining, it is important to develop the economy on the basis of innovative factors.The article also shows the state support for the formation of an innovation strategy in Uzbekistan and its main directions.